2019
DOI: 10.1016/j.chom.2018.12.001
|View full text |Cite|
|
Sign up to set email alerts
|

HIV-1 Neutralizing Antibody Signatures and Application to Epitope-Targeted Vaccine Design

Abstract: SummaryEliciting HIV-1-specific broadly neutralizing antibodies (bNAbs) remains a challenge for vaccine development, and the potential of passively delivered bNAbs for prophylaxis and therapeutics is being explored. We used neutralization data from four large virus panels to comprehensively map viral signatures associated with bNAb sensitivity, including amino acids, hypervariable region characteristics, and clade effects across four different classes of bNAbs. The bNAb signatures defined for the variable loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
156
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 97 publications
(170 reference statements)
13
156
1
Order By: Relevance
“…As an example, Figure 6B shows the shortest paths to all glycans from the glycan at site N332. The site N332 is central in the glycan interaction network, and is known to have both direct and subtle long-range influences over a number of bNAb sites[7, 69]. Our calculation shows the most probable pathway over which each glycan feels the influence of the glycan at site N332.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As an example, Figure 6B shows the shortest paths to all glycans from the glycan at site N332. The site N332 is central in the glycan interaction network, and is known to have both direct and subtle long-range influences over a number of bNAb sites[7, 69]. Our calculation shows the most probable pathway over which each glycan feels the influence of the glycan at site N332.…”
Section: Resultsmentioning
confidence: 98%
“…While each glycan exerts effects in its immediate vicinity, due to the inter-glycan interactions, their influence can percolate over long distances across the surface of protein. Long-range glycan interactions can occur, as with perturbation of a glycan at one site can affect the processing and antibody interactions of another glycan at a distant site[7, 18, 23, 69]. Understanding long-range interactions between glycans is important for characterizing global properties of the glycan shield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further enhance potency, more than three Fabs could be joined together into a multiFab. By joining multiple types of Fabs that bind to different epitopes (e.g., the broadly neutralizing CD4binding 3BNC117 with a V1V2-binding PG16), multiFabs may enhance the potency of neutralization as well as help combat HIV-1 heterogeneity as has been seen in combination influenza antibodies (51) and HIV-1 mosaic vaccines (52).…”
Section: The Avidity Of a Trifab Is Capable Of Binding Three Env Sitementioning
confidence: 99%
“…High-resolution imaging approaches have revealed that bNAb and glycan interactions are common across all bNAb classes, and previous analyses to map antibody binding and antibody neutralization activity depended not only on sequence, but also on glycan occupancy (18,19). Computational approaches for prediction of neutralization sensitivity based on Env sequences have been reported previously (20)(21)(22). Information of glycans and glycan occupancy, however, have not been included in these models, therefore excluding a critical component.…”
Section: Introductionmentioning
confidence: 99%